Compilations of Losses [Recolecciones de Pérdidas] - Cussen-Abud, F (Universidad de la Serena,Departamento de Artes y Letras, 2020)
The category “compilations of losses” refers to a series of books that compile literary, visual, cinematographic, photographic or musical works that we can t read, see or listen to. In this essay I gather a large number of them, in order to analyze their characteristics and interpret the effects they seek to provoke in the reader. © 2020 Logos: Revista de Linguistica, Filosofia y Literatura. All rights reserved.